Automatic Electronic Device Used for the Evaluation of Cyclic-Fatigue Resistance of Nickel-Titanium Instruments - Gaitán-Fonseca DDS, MSc, PhD, Cesar (2017)
The aim of this study was to evaluate the cyclic-fatigue fracture of different Nickel-Titanium motor-driven rotary instruments (ProTaper® Universal, ProFile®, and Mtwo® systems) in artificial canals by means of an Automatic Electronic Device (AED). The study was performed using Nickel-Titanium instruments 25/0.06 evaluated in canals with a 45-degree curvature and 2-mm radius. The analyses evaluated two parameters: fracture by cyclic fatigue, and time of fracture; in addition, the length of separated fragment was evaluated. Medians and range values were calculated for each group. Data were analyzed by the Kruskall–Wallis and Mann–Whitney U tests to determine statistical difference. The ProFile motor-driven rotator system exhibited highest resistance to fracture due to cyclic fatigue and highest fracture time compared with the ProTaper and Mtwo systems (p <0.05). The equipment proposed in this study (AED) demonstrated efficiency for recording information, automation, scheduled work times and durations, cycle number, time of fracture, pressure changes and, principally control of the human factor.